Peningkatan Daya Saing UMKM Sarana Upakara Melalui Digitalisasi Katalog Produk dan Strategi Pemasaran Berbasis Digital - Ni Kadek Tasya Novita Devi; I Putu Agus Eka Yatna Cipta; I Komang Budi Mas Aryawan; I Ni Komang Nandita Putri Wiardani; Celvina (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The partner in this Community Partnership Program is a MSME engaged in the sale of Balinese ceremonial equipment, namely Toko Windu Sarana Upakara. The main problems faced by the partner include: (1) limited understanding and skills in utilizing digital technology, particularly in creating a product catalog, and (2) insufficient knowledge of digital marketing strategies, which has restricted their market reach to the local neighborhood. The objectives of this PKM are: first, to improve the partner’s understanding of product marketing through digital catalogs, with an achievement target of 80–100%; and second, to enhance the partner’s ability to implement marketing strategies using WhatsApp Business, also with a target of 80–100% understanding and application. The program involved two participants. The implementation method consisted of four stages: planning, execution, evaluation, and reflection. The results indicated: (1) the successful development of a product logo and a digital catalog for Toko Windu Sarana Upakara, and the smooth execution of digital marketing training using WhatsApp Business; (2) prior to the training, the partner lacked knowledge about brand image and the importance of branding, but afterward, all participants (100%) demonstrated a good understanding of these concepts; (3) initially, the partner had limited skills in using WhatsApp Business for handling customer orders, but after the training, all participants (100%) were able to use the platform effectively.